FEATURES OF THE CLINICAL COURSE AND COMPLEX TREATMENT OF HEMORRHOIDS IN CHILDREN - А.Ж. Хамраєв; С.Ш. Джораєв (Bukovynian State Medical University, 2022)
The aim: to analyze the current state of the issue of hemorrhoid disease in children of different age on the basis of first-hand experience. Materials and methods: author conducted examinations in 71 children with hemorrhoids: general clinical, laboratory, rectal finger, anoscopy, rectoscopy and additional research complexes. There were 56 (78,8%) boys and 15 (21,2%) girls. Results and discussion: The features of the cause of the disease, clinical manifestation, course, localization have been studied and tactical treatment approaches in the age aspect have been developed. In infants, a common cause of hemorrhoids were: a two-stage act of defecation with increased diarrheal syndrome; in children of early and preschool age, periodic and prolonged potty sitting and congenital inferiority of the venous network of the small pelvis in schoolage children played an important role. The frequency of occurrence is more marked in preschool age - 71.7%. The external form of hemorrhoids was revealed - in 90% and combined - in 10% of sick children. Frequent localization of hemorrhoids occurred in children at 4 o'clock (35%) and 7 o'clock (30%). Comprehensive treatment of hemorrhoids in children was carried out: conservative - in 34 (83%) and surgical - in 7 (17%) patients. In infancy and early age, the complex of conservative treatment included: treatment of the main primary disease (ChD, diarrheal syndrome, pathology of the colon, etc.) and local treatment; in preschool children - the use of medical enemas and rectal suppositories, ointments and the use of SCL, LL and school and older age - treatment of ChD. Indications for the operation were: the presence of large varicose nodes that violate the act of defecation, inflammation, prolapse, infringement and constantly falling out nodes and causing pain. In children, more gentle surgical methods are used. Surgical treatment is more susceptible to school age. There were no complications in the postoperative period. Conclusions. 1. Persistent constipation is a common cause of hemorrhoids in children; increased diarrhea, a two-stage act of defecation, tension in sports, tense cough and urination are also causes of hemorrhoids. 2. The clinical features of the course of hemorrhoids in children 1-3 years old is the transient nature of the course in 70% of cases. 3. Hemorrhoids are often found in children of preschool age, with the absence of pain and bleeding. 4. The most frequent (65%) localization is 4 and 7 on the clock face. 5. In children under 3 years of age with hemorrhoids, only conservative treatment is an effective method. Surgical treatment is more susceptible to school age. 6. Indications for hemorrhoid surgery in children are: the presence of large varicose nodes that violate the act of defecation, inflammation, prolapse, infringement, as well as easily or constantly falling out nodes and causing pain.